Prophylactic intravenous norepinephrine for the prevention of hypotension during spinal anesthesia for elective cesarean section: a systematic review and dose–response meta-analysis of randomized controlled trials - Li, Yuan; Shuai, Bingxing; Huang, Han (Frontiers in Pharmacology, 2023)
Introduction We aimed to evaluate the potential dose-response relationship between prophylactic norepinephrine (NE) infusion rates and the risks of hypotension during cesarean section following spinal anesthesia. Method Randomized controlled trials with two or more NE doses for post-spinal hypotension prophylaxis during cesarean section were systematically searched in database of MEDLINE, EMBASE, Web of Science, Cochrane Central Register of Controlled Trials, and U.S. clinical trials registry were searched till 31st July 2022. The primary outcome was the relative risk of maternal hypotension with different NE regimens (infusion rates or bolus doses). Secondary outcomes included the relative risks of maternal and fetal adverse events with different NE regimens. Results Ten studies with 1144 parturients were included for final analysis using restricted cubic splines and random effects dose-response meta-analysis models. Significant dose-response relationship existed between NE infusion rates and the relative risks of maternal hypotension. Every 0.01μg/kg/min increment in NE infusion rate was associated with a 14% decrease in incidence of post-spinal hypotension. ED50 and ED95 of NE infusion rates for post-spinal hypotension prophylaxis were estimated to be 0.046 (95%CI from 0.032 to 0.085) and 0.2 (95%CI from 0.14 to 0.37) μg/kg/min, respectively. However, higher NE infusion rate was associated with higher incidence of maternal hypertension. Conclusion Increased NE infusion rate was associated with a decreased incidence of post-spinal hypotension but an increased incidence of hypertension. Therefore, 0.07 μg/kg/min was recommended as the initial NE infusion rate for clinical practice, as it was associated with the lowest risk of physician intervention for unstable hemodynamics after spinal anesthesia for cesarean delivery.